Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.3390/jpm13030564
|View full text |Cite
|
Sign up to set email alerts
|

Balloon Dacryocystoplasty with Pushed Monocanalicular Intubation as a Primary Management for Primary Acquired Nasolacrimal Duct Obstruction

Abstract: Given the improvement in the instrument and techniques, novel surgical interventions emerged to avoid the osteotomy from the gold standard dacryocystorhinostomy (DCR) for treating primary acquired nasolacrimal duct obstruction (PANDO). This study’s aim is to compare the surgical outcomes of antegrade balloon dacryocystoplasty (DCP) with pushed monocanalicular intubation (MCI) to balloon DCP alone in patients with complete PANDO. Adult patients with complete PANDO receiving balloon DCP followed by pushed MCI or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…It may also be used for the treatment of adult patients with partial nasolacrimal duct obstruction, especially in those who are poor candidates for dacryocystorhinostomy or general anesthesia [ 13 ]. Lai et al found that balloon dacryocystoplasty (DCP) with pushed monocanalicular intubation in adults aged under 65 with complete primary acquired nasolacrimal duct obstruction can achieve a higher success rate than those who underwent balloon dacryocystoplasty alone [ 14 ].…”
mentioning
confidence: 99%
“…It may also be used for the treatment of adult patients with partial nasolacrimal duct obstruction, especially in those who are poor candidates for dacryocystorhinostomy or general anesthesia [ 13 ]. Lai et al found that balloon dacryocystoplasty (DCP) with pushed monocanalicular intubation in adults aged under 65 with complete primary acquired nasolacrimal duct obstruction can achieve a higher success rate than those who underwent balloon dacryocystoplasty alone [ 14 ].…”
mentioning
confidence: 99%